Analisis Modul Matematika Berbasis PBL dalam Meningkatkan Mathematical Habits of Mind di Kelas IV Sekolah Dasar - Rokhmatun Nabillah (LPPM UNU CIREBON, 2025)
The low achievement not only shows the limitations of mastering mathematical concepts and procedures, but is also closely related to the undeveloped habits of mind in mathematics learning. So in this study it aims to analyze PBL-based mathematics modules to improve Mathematical Habits of mind in Class IV of SD Kartika Cirebon Kota. The research method used in this study is quantitative research with a quasi-experimental research design. The population in this study is students and students of SD Kartika Cirebon Kota, the sample selection technique uses cluster sampling so that class IV A is chosen as the Experiment class and Class IV B as the control class. Non-test data collection technique with questionnaires. The data analysis technique uses the T Test with the help of SPSS. The results of this study using a paired sample t-test showed a difference between the initial questionnaire score and the final questionnaire in both the experimental and control classes. This can be seen from the significance value of Sig. (2-tailed) which is smaller than 0.05 (Sig. < 0.05), so that the average difference between the initial and final measurements in the two classes is stated to be significant at the level of 5%. The mean value of change in the experimental class was greater than that of the control class, which was -30.62 in the experimental class and -5.66 in the control class. The conclusion of this study is that the use of problem-based learning-based mathematics modules has a significantly stronger influence on the experimental class compared to the control class. This finding is supported by the acquisition of a higher average score of the experimental class, so it can be affirmed that learning with a problem-based learning mathematics module is more effective in improving the ability of mathematical habits of mind.